Instructional Strategy for Teaching Children with Autism in the Classroom - Anindita Lintangdesi Afriani; Fitria Ayuningtyas; Putrawan Yuliandri (Jurnal Indonesia Sosial Teknologi, 2025)
This research looks at a number of persons who have communication problems due to various diseases. Children with autism are one of them. Because children with autism have three basic disorders: communication, social interaction, and behavior, their communication and social interaction will undoubtedly differ from those of typical children. This research will look into instructional communication for children with autism in the classroom at Rumah Autis Depok. Rumah Autis is a social institution created to fill the gap between the demand for therapeutic locations and schools for children with autism and special needs who come from low-income households. The ethnography of communication approach was used in this research because ethnography of communication focuses on communication processes that involve language and culture. The findings of this research indicated that the communication utilized by children with autism, particularly instructional communication in the classroom, is quite unique and distinct. Teachers must speak firmly but not loudly or repeatedly. Therefore, the students easily understand. Children with autism are easily distracted, and thus, the teacher does not allow wearing eye-catching clothing and headscarves in class. The research encourages communication ethnographers to reflect on fieldwork issues and gives a framework for doing so, particularly when it comes to teaching children with autism